ANALISIS KETERBUKAAN INFORMASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA HAMBAWA KECAMATAN GUNUNGSITOLI UTARA KOTA GUNUNGSITOLI - ROHMAT POLINUS ZILIWU; EMANUEL ZEBUA; NOVELINA ANDRIANI ZEGA (JURNAL ILMIAH SIMANTEK, 2022)
The purpose of this study is to examine the disclosure of information carried out by the Hambawa Village Government, North Gunungsitoli District, Gunungsitoli City in increasing community participation in Hambawa Village. The research method used in this research is descriptive qualitative. The object of this research was carried out at the Hambawa Village Government Office, North Gunungsitoli District, Gunungsitoli City, namely from October to November 2022. The informants who were the sources in this study were information disclosure in increasing community participation in Hambawa village including: Village Heads, Village Apparatus and community leaders. Sources of data in this study are primary data and secondary data. Information disclosure in increasing community participation in Hambawa Village, North Gunungsitoli District, Gunungsitoli City is considered good. This is evidenced by the increasing participation of the community in involving themselves in the implementation of Village Government activities. Information disclosure in Hambawa Village, North Gunungsitoli District, Gunungsitoli City is considered to have been carried out in accordance with applicable laws and regulations.